Transitional Opportunities of the Family Farms to Agribusiness in Livestock Production in Cameroon - Mbu Daniel Tambi; Forchid Julius Anyah (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2020)
This study seeks to catalogue the opportunities for livestock production in the North West Region of Cameroon. Using Google Earth Maps, twenty urban and twenty peri-urban points were randomly selected based on settlement, followed by a random selection of four livestock farmers per point to participate in this study. A random sample of 160 questionnaires was collected and analysed using the Statistical Package for the Social Sciences version 20.0. The result showed that farmers kept a variety of livestock species of which most were pigs followed by poultry. Although poultry were the second most common species kept, they were more important than all other species in the livelihoods of farmers due to their multiple roles. This study suggests that information on innovations in livestock production should be available to farmers to improve their production and sales.